Polyjet 3D printing for 3D structure fabrication of microfluidic device channel - Lio, Chin How (2017)
Fabrication of microfluidic devices for use in biomedical research using three-dimensional (3D) printing has been gaining popularity in recent years. The advantages over the conventional method of soft lithography include the ability to construct complicated structures, rapid building time and relative simplicity in operation. Despite the benefits, the application of 3D printing in microfluidics has limitations. Most 3D printers are unable to produce smooth vertical surfaces due to its inherent nature of processing layer upon layer of material one on top of another. While this surface roughness is insignificant in large structures, it becomes apparent in microfluidic devices and can have a negative effect on those where functionality depends on well-defined features. One such microfluidic device is a curved microchannel used for separating particles of different sizes in fluid flow. It utilises a combination of inertial lift forces and secondary Dean flows to focus the particles into different streams determined by their size, which are then collected via different outlets. These two forces are highly dependent on channel dimensions, therefore poorly-defined features like the sidewalls of the channel may affect their magnitude and impede particle separation. This study was carried out to investigate the viability of using an inkjet 3D printer to fabricate functional microchannels that can be used to separate particles in fluid flow. A curved microchannel was designed based on theoretical calculations and printed using a ProJet 5500X 3D printer. The resulting product was unsatisfactory and could not be tested in experiment. Focus was then shifted to using simulation software COMSOL to design the microchannels. The dimensions were based around the minimal attainable feature size of the ProJet 5500X. In COMSOL, particle separation was simulated and to achieve the best separation efficiencies, fluid velocity and microchannel dimensions were continuously adjusted following the result of a simulation. One model which performed favourably was printed by the ProJet 5500X and an experiment replicating simulation conditions was carried out. Experiment results showed that although not completely separated, there was still a good degree of inertial migration observed in the larger particles. The incomplete separation was attributed to an overly high concentration of smaller particles used in the particle mix and some rough features along the microchannel walls. Nevertheless, the preliminary experiment result indicates that inkjet 3D printing has potential to fabricate accurate features in the micro-scale as required by devices that function on the principle of inertial microfluidics.